Macro modelo de biblioteca inteligente para la Facultad de Energía, las Industrias y los Recursos Naturales no Renovables del campus universitario - Narváez Castillo, Kelly Paulina (2020)
The aim of the present degree work is to build the macro model of an intelligent library, focused to the Faculty of Energy, Industries and Non-Renewable Natural Resources (FEIRNNR) of the National University of Loja (UNL). In order to achieve this objective, the real setting of the case study was diagnosed: “the FEIRNNR-UNL library”, from which it was mentioned that the lack of services, learning spaces and staff to address the needs of the user, have caused a low impact of the library as a learning center inside the UNL; after that, a Systematic Literature Review (SLR) was developed with the selection of 28 primary studies, from which it was reached as a result that, the intelligent library interconnects services, spaces and people through emergent technologies, being considered as its requirements. The requirements to develop the intelligent library model, were specified based on the literature review of 15 academic libraries of the Higher Education Institutions (IES), at the world level, dedicated to the study area of “Engineering & Technology”; where, learning, research and user welfare are the focus of intelligent services; intelligent spaces are adapted to diverse types of learning; library staff contrast people with the capacity to constantly learn, and the interconnected cutting-edge technologies form the Internet of things (IoT) as a solution for automation, management and intelligent communication between services, spaces and people. Finally, the use intention of the FEIRNNR-UNL library users facing to an intelligent library model, was examined by analyzing their perception, using the Technology Acceptance Model (TAM) and the application of the PLS-SEM technique; With this, it was evidenced that the intention of use is influenced in greater significance by the attitude towards use and the perceived ease of use, and in less significance by the perceived utility; therefore, TAM was considered a valid model to explain the user's intention to use the intelligent library in a real context.